Nutritive value of high and low tanin content of sorghum high moisture silage for horses - doi: 10.4025/actascianimsci.v35i1.10575 - Kátia de Oliveira; Ciniro Costa; Carla Maris Machado Bittar; Vinícius Antonio Baptista Oliveira; Janaina Carolina de Sá (Acta Scientiarum. Animal Sciences, 2012)
There were used eight castrated male horses, crosbred. It was used randomized completely design.  The objective was to evaluate the nutritive value of high-moisture grains silage of sorghum with low (SLT) and high (SHT) tannin in the feeding equine. The treatments consisted of two test-diets containing SLT or SHT, replacing 30% of dry matter (DM) of the reference-diet, constitued by only hay. The values of digestibility coefficients (DC) of nutrients SLT and SHT had differences for DCDM, DCOM, DCCE, DCCP and DCStarch, whose means values were 79.53, 84.54, 79.36, 76.11 and 100% to SLT e 60.29, 64.47, 59.38, 44.63 and 97.06% to SHT, respectively. It was concluded that high-moisture grains silage of sorghum with low tannin should be used in equine nutrition, this is an alternative feed.